Small complements of Ps and genitive case assignment - Pleshak, Polina (Proceedings of the Linguistic Society of America, 2023)
This paper deals with possessor case assignment in Samburg Izhma-Komi subjects and oblique nominals. The problem is that the case assigned to the possessor depends on the syntactic position of the enclosing nominal; possessors are genitive in subjects and nominative in obliques. This is not predicted by the current theories of case. Looking at morphosyntactic properties of P-complements in Samburg Komi such as possessive agreement within the complement, possessive agreement with the complement, and plural marking of the complement, I show that these complements are not full DPs. The possessor case-marking follows straightforwardly. Since P-complements are not DPs, as opposed to subjects, genitive cannot be assigned. Independently, I show that nominative is the case assigned in PPs. In absence of a D, the case associated with P is assigned to possessors in obliques. This analysis has several theoretical implications. First, I show that inherent cases are better analyzed as syntactic P-heads alongside free-standing postpositions. Second, I provide an argument in favor of DP-hypothesis. Finally, I show that not all arguments within a language must be full DPs.